Emerging infectious diseases – 1970s. Issue 5 (1st January 2016) - Ferguson, Robert
Abstract : Forty years ago is not ancient history in the medical field. However, being an eye witness to the emergence of three new infectious diseases in the northeastern United States in the 1970s left a deep impression on this author. I will relate a small portion of the amazing events that caught the attention of the medical establishment and the general public in a roughly 5-year period of medical discovery.